Spironolactone metabolite concentrations in decompensated heart failure: Insights from the ATHENA-HF trial. - de Denus, Simon (Eur J Heart Fail, 2020)
BACKGROUND. In Aldosterone Targeted Neurohormonal Combined with Natriuresis Therapy in Heart Failure (ATHENA-HF), high-dose spironolactone (100 mg daily) did not improve efficacy endpoints over usual care (placebo or continued low-dose spironolactone [25 mg daily] in patients already receiving spironolactone) in the treatment of acute heart failure (HF). We hypothesized that low concentrations of the long-acting active metabolites of spironolactone (canrenone and 7-α-thiomethylspironolactone [7α-TMS]) in the high-dose group could have contributed to these neutral results. METHODS AND RESULTS. In patients randomized to high-dose spironolactone not previously treated with spironolactone (high-dose-naïve, n=112), concentrations of canrenone and 7α-TMS increased at 48 and 96 hours compared to baseline, and between 48h and 96h (all p<0.005), indicating that steady-state concentrations had not been reached by 48h. In patients previously on low-dose, high-dose spironolactone (high-dose-previous, n=37), concentrations of canrenone increased at 48h and 96h compared to baseline (both p<0.0005), with a marginal increase between 48h and 96h (p=0.0507). At 48h, both high-dose groups had higher concentrations of both metabolites than the low-dose spironolactone group (p<0.0001). Moreover, concentrations of both metabolites were higher in high-dose-previous vs. high-dose-naïve patients (p<0.01), indicating that previous spironolactone use was significant, and that steady-state has not been reached in high-dose-naïve patients at 48h. We found limited and inconsistent evidence of correlation between metabolite concentrations and endpoints. CONCLUSIONS: Lower-than-anticipated concentrations of spironolactone active metabolites were observed for at least 48h in the high-dose spironolactone group and may have contributed to the absence of pharmacological effects of spironolactone in the ATHENA-HF trial.